Narrow-leafed lupin (Lupinus angustifolius L.) ß-conglutin proteins modulate the insulin signaling pathway as potential type 2 diabetes treatment and inflammatory-related disease amelioration - Lima-Cabello, E.; Alche, V.; Foley, R.; Andrikopoulos, S.; Morahan, G.; Singh, Karam; Alche, J.; Jimenez-Lopez, J. (Wiley - V C H Verlag GmbH, 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.Scope: We have investigated the potential use of ß-conglutin protein isoforms from narrow-leafed lupin (Lupinus angustifolius L.) as a diabetes treatment. Methods and results: We produced purified recombinant ß1-, ß2-, ß3-, ß4-, and ß6-conglutin proteins and showed that ß1, ß3, and ß6 could bind to insulin. To assess ß-conglutin proteins modulatory effect on insulin activation meditated kinases, whole blood and peripheral blood mononuclear cell cultures from type 2 diabetes (T2D) and healthy control subjects (C) were incubated with conglutin proteins. The treatment of peripheral blood mononuclear cells from T2D patients with ß1, ß3, and ß6 proteins increased up to threefold mRNA and protein levels of genes important in insulin signaling pathways, namely insulin receptor substrate 1/p85/AKT/glucose transporter type 4. This was accompanied by a comparable fold-change decrease in the mRNA expression level of pro-inflammatory genes (iNOS and IL-1ß) and proteins compared to healthy controls. The ß2 and ß4 isoforms had no effect on the insulin signaling pathway. However, these ß-conglutin proteins elicited pro-inflammatory effects since levels of mRNA and proteins of inducible nitric oxide synthase and IL 1 beta were increased. Conclusion: Our results raise the possibility of using these particular ß-conglutin proteins in the prevention and treatment of diabetes, as well as their potential as anti-inflammatory molecules.